2013
DOI: 10.1371/journal.pone.0068273
|View full text |Cite
|
Sign up to set email alerts
|

Axial Low Back Pain: One Painful Area – Many Perceptions and Mechanisms

Abstract: Axial low back pain can be considered as a syndrome with both nociceptive and neuropathic pain components (mixed-pain). Especially neuropathic pain comprises a therapeutic challenge in practical experience and may explain why pharmacotherapy in back pain is often disappointing for both the patient and the therapist. This survey uses epidemiological and clinical data on the symptomatology of 1083 patients with axial low back pain from a cross sectional survey (painDETECT). Objectives were (1) to estimate whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 38 publications
1
51
0
4
Order By: Relevance
“…Our results strongly demonstrated the potential of TSA for the treatment of IVD degeneration-related back pain. Both nociceptive and neuropathic pathophysiological mechanisms are involved in the development of back pain [35,36], and IVD degeneration is the major underlying cause. IVD degeneration is induced by phenotypic changes in the NP cells, which cause tissue degradation [4] and neoinnervation of the disc, contributing to the transmission of pain in vivo [37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results strongly demonstrated the potential of TSA for the treatment of IVD degeneration-related back pain. Both nociceptive and neuropathic pathophysiological mechanisms are involved in the development of back pain [35,36], and IVD degeneration is the major underlying cause. IVD degeneration is induced by phenotypic changes in the NP cells, which cause tissue degradation [4] and neoinnervation of the disc, contributing to the transmission of pain in vivo [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, back pain is caused by complex interactions of biological, psychological and social factors, and therefore it is considered as a syndrome with both nociceptive and neuropathic components involved in [35]. Nociceptive nerves are a major transmitter of discogenic back pain, therefore alteration of nerve growth into the disc by TSAmediated inhibition of neurotrophins can modulate the development of acute and chronic nociceptive pain [47].…”
Section: Discussionmentioning
confidence: 99%
“…As was also noticed during the panel discussions, some of these may need further refinement. This is particularly true for the concept of neuropathic (versus nociceptive or mechanical) pain for which there is currently much debate on its precise nature [14,[42][43][44][45] and role in the diagnostic evaluation and treatment choice for patients with PPSS [12-14, 46, 47]. Further research may also consider the inclusion of additional somatic variables, potentially relevant to treatment choice, such as sagittal balance [15,16].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Given that patients with mixed pain syndromes may have extended periods in which either neuropathic or nonneuropathic components predominate (ie, someone with degenerated disks and nerve root involvement may experience only occasional radicular symptoms), it is likely that their instrument-derived pain scores would fall into the intermediate range between the 2 discrete categories. In a large-scale study that sought to identify neuropathic pain in individuals with purely axial low-back pain, Förster et al 46 found a 12% incidence based on the painDETECT questionnaire. So whereas it is logical to conclude that pain scores intermediate between likely and unlikely neuropathic pain suggest a "mixed" condition, this contention remains speculative.…”
Section: Limitationsmentioning
confidence: 99%